Is Islamic Banking Capable of Meeting Corporate Social Responsibility? (International Journal of Banking and Finance, 2013)
This paper provides an overview of the Islamic banking system and its product ranges, and examines their ability to meet Corporate Social Responsibility obligations while maintaining efficiency and managing risk. The growing literature on Islamic banking products, including their derivatives indicates that Islamic banking is popular worldwide and has global attention. Similarly, the diversity of banking options is growing in Middle Eastern countries with some banks offering separate windows for conventional and Islamic banking options to customers. Due to the unique nature of Islamic banking, which is constrained not only by the standard operating regulations of the respective countries, but also by Islamic law, the Sharī’ah, there are significant differences in the philosophy behind its finance transactions, the nature of transactions, goals and the obligations between the two types of institutions. Whether these differences lead to changes in risk preferences, lending decision-making processes, and the ultimate efficiency of operations are some of the key empirical questions yet to be fully answered. The paper introduces a theory based on classical utility theory, and then extends it to show its relevance to Islamic banking. In particular this paper shows that Islamic banking may not only improve operating performance, but also increase profitability for all parties concerned.